Digitisation of Peruvian satirical newspapers, 1822-1918 - (:unkn) unknown (My University, 2026)
This pilot project aims to digitise 24 titles including Peruvian newspapers and magazines from 1822 to 1918, which contain information on political press, social life, and customs through illustrations and satirical texts about the government, public figu